2019
DOI: 10.1002/dvdy.76
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone coordinates developmental trajectories but does not underlie developmental truncation in danionins

Abstract: Background Differences in postembryonic developmental trajectories can profoundly alter adult phenotypes and life histories. Thyroid hormone (TH) regulates metamorphosis in many vertebrate taxa with multiphasic ecologies, and alterations to TH metabolism underlie notable cases of paedomorphosis in amphibians. We tested the requirement for TH in multiple postembryonic developmental processes in zebrafish, which has a monophasic ecology, and asked if TH production was compromised in paedomorphic Danionella. Resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…This decoupling may indicate the timing of the metamorphosis of A. ocellaris, which would be mainly characterized by pigmentation changes and not by drastic morphological changes, as it has been observed in grouper, flatfish, or surgeonfish . In those species, it is known that thyroid hormones are controlling metamorphosis as in amphibians, and it has been shown that these hormones markedly affect overall growth and development rates, as well as individual traits including pigmentation and scales, feeding kinematics, and morphometrics and the lateral line . It is similarly likely that thyroid hormones control the morphological and pigmentation changes that occur during A. ocellaris metamorphosis.…”
Section: Discussionmentioning
confidence: 88%
“…This decoupling may indicate the timing of the metamorphosis of A. ocellaris, which would be mainly characterized by pigmentation changes and not by drastic morphological changes, as it has been observed in grouper, flatfish, or surgeonfish . In those species, it is known that thyroid hormones are controlling metamorphosis as in amphibians, and it has been shown that these hormones markedly affect overall growth and development rates, as well as individual traits including pigmentation and scales, feeding kinematics, and morphometrics and the lateral line . It is similarly likely that thyroid hormones control the morphological and pigmentation changes that occur during A. ocellaris metamorphosis.…”
Section: Discussionmentioning
confidence: 88%
“…Thyroid hormones are important for regulating sensory development in teleost fishes 11,14,36,38 , and our results provide insights into the role they play in this development during recruitment. A. triostegus exhibits an enclosed nose (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Surprisingly, the ultimate consequences of stressor-induced developmental and endocrine impairments, such as their impact on predator-prey dynamics, remain poorly studied 34 . TH plays a key role in neurogenesis and sensory development in vertebrates 35,36 , and are central for regulating recruitment in reef fishes 11 . Thus, TH signaling disruption may present a generalizable physiological mechanism through which reports of behavioral and survival deteriorations in recruiting fishes following exposure to anthropogenic stressors can be understood 34 .…”
mentioning
confidence: 99%
“…Thyroid hormone (TH) is an essential regulator of cellular metabolism and homeostasis, and coordinates developmental events in diverse vertebrates (McMenamin and Parichy, 2013; Shi, 2013; Buchholz, 2015). In zebrafish, the hormone regulates numerous aspects of post-embryonic development (McMenamin et al, 2014; McMenamin et al, 2017; Hu et al, 2019; Keer et al, 2019; Saunders et al, 2019). In hypothyroid zebrafish, we observed changes in the fin skeleton consistent with shifts in axis polarity, and we hypothesized that TH regulates proximodistal identity of the fin rays.…”
Section: Introductionmentioning
confidence: 99%